Design a very short introduction - Heskett, John. (Oxford : Oxford University Press, 2005)
This title transforms the way we think about design. How does design affect our everyday activities? Do we appreciate its place in our daily lives? Simple objects, such as a spoon, can have their design modified to meet the needs of specific cultural behaviour.
Originally published: 2002.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Design